Pembentukan Karakter Anak dalam Keluarga Kristen di Era Digital: Studi Deskriptif pada Orang Tua Jemaat - Eunike Eunike; Lidiawati Lidiawati; Matius Kalatiku (Pusat Riset dan Inovasi Nasional, 2026)
This study explores the dynamics of children’s character formation within Christian families in the digital era from the perspective of church parents. Employing a descriptive light mixed-methods design, the study integrates survey data and semi-structured interviews to obtain both quantitative and qualitative insights. The findings indicate that digital media has become an integral and unavoidable part of family life, making children’s character formation highly dependent on parental guidance, reflective communication, and consistent faith-based education at home. Parents face various challenges related to time constraints, limited digital literacy, and the increasing exposure of children to external values that may not align with Christian teachings. At the same time, many parents actively utilize technology as a supportive and accessible tool for spiritual learning and moral development. The study concludes that character formation is shaped not merely by technology itself but more significantly by the quality of family relationships and parental role modeling grounded in Christian values. Therefore, the findings recommend strengthening faith-based digital literacy among parents and enhancing church–family collaboration to foster more holistic, balanced, and sustainable character development in children.